The Hispanic community and the role of women in Chicana literature - Chárová, Denisa (Univerzita Pardubice, 2021)
This thesis deals with the portrayal of the Hispanic community and the role of women in Chicana literature. It is divided into a theoretical and a practical part. The theoretical part introduces the historical and literary context of Hispanic literature. The practical part then focuses on the analyses of the two chosen works - The House on Mango Street by Sandra Cisneros and So Far from God by Ana Castillo. The analysis is aimed at the authors' portrayal and commentary on issues surrounding Hispanic people living in the United States and the portrayal of women in their works.
Hispánská komunita a role žen v americko-hispánské literatuře
Keywords: ženské postavy; genderové role; etnicita; menšina; hispánská literatura; female characters; gender roles; ethnicity; minority; hispanic literature